Acoustic Horn Design and Effects of Process Parameters on Properties of Dissimilar Ultrasonic Welding Aluminum to Brass. Issue 3 (17th February 2016) - Satpathy, M. P.; Sahoo, S. K.; Datta, S.
Abstract : Ultrasonic welding technology is a new and emerging concept, which can be applied to many industrial applications. The vital part of this technology is the horn, which acts as a tool, upon which the pressure and high-frequency vibration is applied to create a solid-state weld. In this study, a special type of horn is designed and its length is determined analytically. Dimensions obtained by finite-element method (FEM) are employed for the horn used in the present experiments to weld brass with aluminum sheet of thickness 0.1 mm. The dynamic analysis is also performed to find out the stress and amplitude distribution in the horn under loading conditions. Welding has been carried out using various parameter combinations in order to improvise the weld strength. Maximum weld strength of 4.05 MPa is obtained under the optimum welding conditions of 0.21 s weld time, 0.26 MPa weld pressure, and 60 µm vibration amplitude. The microhardness test also has been done on the optimized results to show the plastic flow at the weld zone. It confirms that the hardness of both materials up to 20 µm distance around the weld zone is increased with respect to the parent materials.